2002
DOI: 10.1002/jnr.10472
|View full text |Cite
|
Sign up to set email alerts
|

Mature myelin basic protein‐expressing oligodendrocytes are insensitive to kainate toxicity

Abstract: We examined the vulnerability to excitotoxicity of rat oligodendrocytes in dissociated cell culture at different developmental stages. Mature oligodendrocytes that express myelin basic protein were resistant to excitotoxic injury produced by kainate, whereas earlier stages in the oligodendrocyte lineage were vulnerable to this insult. To test the hypothesis that the sensitivity of immature oligodendrocytes and the resistance of mature oligodendrocytes to kainate toxicity were due to differences in membrane res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
100
0
1

Year Published

2004
2004
2008
2008

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 124 publications
(107 citation statements)
references
References 50 publications
6
100
0
1
Order By: Relevance
“…This study used the oligodendroglial cell line OLN-93 (Richter-Landsberg and Heinrich, 1996). Previously studied examples of maturation-dependent toxicity in OLs have not been found to be caspase dependent (Back et al, 1998;Rosenberg et al, 2003;Baud et al, 2004b). The goal of the present study was to examine whether this maturation and caspasedependent vulnerability could also be observed in primary OLs and also to characterize the oxidative stress that is involved upstream of the apoptotic pathway.…”
Section: Discussionmentioning
confidence: 87%
“…This study used the oligodendroglial cell line OLN-93 (Richter-Landsberg and Heinrich, 1996). Previously studied examples of maturation-dependent toxicity in OLs have not been found to be caspase dependent (Back et al, 1998;Rosenberg et al, 2003;Baud et al, 2004b). The goal of the present study was to examine whether this maturation and caspasedependent vulnerability could also be observed in primary OLs and also to characterize the oxidative stress that is involved upstream of the apoptotic pathway.…”
Section: Discussionmentioning
confidence: 87%
“…Radioactivity of the whole-cell lysate was counted by liquid scintillation. Electrophysiological recordings on pre-OLs were performed using conventional patch-clamp techniques in whole-cell mode as published previously (Dai et al, 2001;Rosenberg et al, 2003). Kainate (100 or 300 M) and topiramate (50 or 100 M; 20 min preincubation) were applied through a gravity perfusion system.…”
Section: Methodsmentioning
confidence: 99%
“…In vitro studies have demonstrated that pre-OLs are more vulnerable to injury than mature OLs under conditions of oxidative stress , oxygen-glucose deprivation (OGD) (Fern and Moller, 2000;Yoshioka et al, 2000;Deng et al, 2003), and glutamate receptor (GluR)-mediated excitotoxicity (Itoh et al, 2002;Rosenberg et al, 2003). Glutamate accumulates in brain under hypoxic-ischemic conditions (Benveniste et al, 1984;Andine et al, 1991;Hagberg, 1992), and excessive activation of GluRs on neurons is a major mechanism in hypoxic-ischemic neuronal death (Choi, 1992;Hagberg et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After this, membranes were rinsed three times for 15 min with TBST and then incubated for 1 h at 20°C with horseradish peroxidase-conjugated antimouse IgG secondary antibody (Jackson ImmunoResearch, West Grove, PA) at a concentration of 1:3000. Blots were again rinsed three times for 15 min each (Rosenberg et al, 2003).…”
Section: Methodsmentioning
confidence: 99%